2016
DOI: 10.1017/s0950268816000212
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of different HIV-1 subtypes in sexual transmission in China: a systematic review and meta-analysis

Abstract: Sexual transmission has become the primary route of HIV transmission in China. Therefore, a comprehensive overview of HIV-1 subtype distribution is necessary for the prevention and control of the HIV epidemic. The present study aimed to provide a comprehensive prevalence estimate of different HIV-1 subtypes in sexual transmission in China. We conducted a systematic literature review for studies of HIV-1 subtypes in English and Chinese through several databases. Eligible articles were screened and selected by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 47 publications
(58 reference statements)
2
30
1
Order By: Relevance
“…A systematic review and meta-analysis conducted in China showed that the pooled prevalence of CRF01_AE, subtype B, CRF07_BC, CRF08_BC, and subtype C was 44.54% (95% CI 40.81–48.30), 18.31% (95% CI 14.71–22.17), 16.45% (95% CI 13.82–19.25), 2.55% (95% CI 1.56–3.73), and 0.37% (95% CI 0.11–0.72), respectively 13 . Notably, the median time from the estimated date of seroconversion to the development of AIDS in the Chinese HIV-1 population was shorter compared with that in other countries 14–16 .…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review and meta-analysis conducted in China showed that the pooled prevalence of CRF01_AE, subtype B, CRF07_BC, CRF08_BC, and subtype C was 44.54% (95% CI 40.81–48.30), 18.31% (95% CI 14.71–22.17), 16.45% (95% CI 13.82–19.25), 2.55% (95% CI 1.56–3.73), and 0.37% (95% CI 0.11–0.72), respectively 13 . Notably, the median time from the estimated date of seroconversion to the development of AIDS in the Chinese HIV-1 population was shorter compared with that in other countries 14–16 .…”
Section: Introductionmentioning
confidence: 99%
“…22 Three HIV-1 Env-pseudotyped viruses were produced in 293T cells by cotransfection with the expression plasmid encoding Env of HIV-1 strains SVPB16 (subtype B), SVPC12 (subtype C) or SH1.81 (CRF01_AE), and the HIV-1 backbone plasmid expressing the entire HIV-1 genome except for Env, pNL4-3Δenv. 23, 24, 25 The pseudoviral particles were collected, titrated and stored at −80 °C until use.…”
Section: Methodsmentioning
confidence: 99%
“…By the end of 2018, the number of people living with HIV (PWH) in China was close to 1.25 million (1,2). The distribution of HIV-1 subtypes in China is diverse with over circulating genetic variants (3), each with an evolving geographical distribution, prevalence and modes of transmission (3)(4)(5)(6). The first nationwide molecular epidemiological survey in 1996-1998 showed that subtype B'/B (47.5%) and subtype C (34.3%) were the most predominant HIV types in China (7).…”
Section: Introductionmentioning
confidence: 99%